MASS TRANSFER COEFFICIENT OF EXTRACTION TANNIN COMPOUNDS FROM PAPAYA LEAVES WITH 96% ETHANOL SOLVENT - Devri Eko Nurwahyuwono; Viola Eka Afrienty; Soemargono Soemargono; Nove Kartika Erliyanti (Konversi, 2021)
Papaya leaves contain antibacterial compounds such as flavonoids, terpenoids, alkaloids, tannins, and saponins.. Tannins are compounds that are often used as antibacterial, antioxidant, pest control, plant fungi, tanners and as a corrosion inhibitor.In this study, the value of the mass transfer coefficient was determined. This study used two varied operating conditions, namely stirring rotational speed (100, 200, 300 rpm) and extraction time (30, 60, 90, 120, and 150 minutes). The extraction process is carried out using a stirred extractor at a temperature of 65 ° C.The value of the mass transfer coefficient obtained is 0.00004 second-1 (100 rpm), 0.00005 second-1 (200 rpm), and 0.00007 second-1 (300 rpm) for the best concentration obtained at 150 minutes with speed turn the stirrer 300 rpm